Analysis of Market Structure and Performance on the Go Public Pharmaceutical Industry in Indonesia - Muhammad Kanzul Fikri; Firmansyah Firmansyah (Universitas Negeri Semarang, 2022)
This study aims to analyze the market structure and examine the main factors that influence the performance of the pharmaceutical industry in Indonesia, these factors are the Market Power Hypothesis (MPH) and the Efficiency Structure Hypothesis (ESH), where the debate between the two perspectives is still going on until now. The Market Power Hypothesis argues that market performance is the result of market power, while the Efficient Structure Hypothesis argues that market performance is a result of the ability to perform efficiency. The variable used to proxy MPH is market concentration, while the ESH is proxied using the variable of technical efficiency and scale. Next, the performance variable used is ROA. The type of data used is secondary data from the annual report of 8 pharmaceutical producers listed on Indonesia Stock Exchange (IDX) from 2010 to 2019. The analytical method used is DEA and panel data regression. The results showed that market concentration negatively affected ROA, while technical efficiency and scale had a positive effect on ROA. These results indicate that the performance (ROA) of the pharmaceutical industry in Indonesia is influenced by the level of efficiency rather than market power, so the results of this study support the Efficiency Structure Hypothesis (ESH) that efficiency is the key to success in the market. These results also support the Chicago School SCP framework that performance determines conduct and then market structure.